2002
DOI: 10.1111/j.1349-7006.2002.tb01324.x
|View full text |Cite
|
Sign up to set email alerts
|

An Anti‐GD2 Monoclonal Antibody Enhances Apoptotic Effects of Anti‐cancer Drugs against Small Cell Lung Cancer Cells via JNK (c‐Jun Terminal Kinase) Activation

Abstract: Small cell lung cancer (SCLC) cell lines specifically express ganglioside GD2, and anti-GD2 monoclonal antibodies (mAbs) caused suppression of cell growth and induced apoptosis of SCLC cells with single use. Here, enhancement of the cytotoxic effects of various anti-cancer drugs with an anti-GD2 mAb was demonstrated. The cytotoxicity of all six drugs examined was markedly enhanced, i.e. 2.4-7.8-fold increase of cell sensitivity in terms of IC 50 . In particular, the combination of cisplatin (CDDP) with an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 46 publications
4
50
0
1
Order By: Relevance
“…Direct apoptotic induction with anti-GD2 mouse mAbs has thus far been reported with GD2-expressing small cell lung carcinoma cell lines (11). Anti-GD2 mAbs binding on the cell surface are thought to cause conformational changes in integrin molecules, leading to the disruption of cell-matrix interactions with subsequent dephosphorylation of focal adhesion kinases (40). In this study, EL4 lymphoma cell apoptosis induced by anti-GD2 mAbs was mainly observed with the murine IgG 3 anti-GD2 60C3 antibody, whereas chimeric c.60C3 had a weak effect at the highest concentration (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Direct apoptotic induction with anti-GD2 mouse mAbs has thus far been reported with GD2-expressing small cell lung carcinoma cell lines (11). Anti-GD2 mAbs binding on the cell surface are thought to cause conformational changes in integrin molecules, leading to the disruption of cell-matrix interactions with subsequent dephosphorylation of focal adhesion kinases (40). In this study, EL4 lymphoma cell apoptosis induced by anti-GD2 mAbs was mainly observed with the murine IgG 3 anti-GD2 60C3 antibody, whereas chimeric c.60C3 had a weak effect at the highest concentration (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Another mechanism contributing to the antitumor effect upon passive immunotherapy with anti-GD2 mAbs involves cell death induction without immune effector mechanism (11,40). Apoptosis induced by anti-GD2 mAbs is very interesting because this mechanism may be very important in the treatment of solid tumors that have evolved complex mechanisms to protect themselves from CDC and ADCC (41).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the anti-proliferative effects of the antibodies are only partially elucidated. In small cell lung cancer cell cultures anti-GD2 ganglioside monoclonal antibodies induced apoptosis through reduction of the phosphorylation levels of focal adhesion kinase (FAK) and the activation of p38 (6) as well as activation of c-Jun N terminal kinase (JNK) (7). Moreover, the anti-GD2 ganglioside mAbs were very efficient in combination with anticancer drugs to exert enhanced cytotoxicity against the afore-mentioned cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evidenced that GD2-specific antibodies inhibit tumor growth without involvement of the immune system (6)(7)(8). The mechanisms of the anti-proliferative effects of the antibodies are only partially elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation